Analisis Tingkat Kepuasan Pasien BPJS Pada Pelayanan Kefarmasian Di Apotek Klinik SATKES PUSDOKKES MABES POLRI - Meila, Okpri; Pontoan, Jenny; Zizwanto, Eddy (Journal of Herbal, Clinical and Pharmaceutical Science (HERCLIPS), 2020)
Service satisfaction is achieved if what the patient gets exceeds what is expected. This study to determine the level of BPJS patient satisfaction and dimensions affect the level of satisfaction with pharmaceutical services provided in Drugstore Clinic Satkes Pusdokkes Headquarter Police. This reasearch was conducted the data of patients who were treated and carried out in cross sectional, by distribution questioner and analyzed descriptive. Reasearch subjects were teken by quota sampling technique. The level of satisfaction of this study was measured based on five dimensions of service quality and analyzed using percentase and likert scalet. The results of the showed that patients who were treated at the Drugstore Clinic Satkes Pusdokkes Headquarter Police were satisfied with the services provided by the services provided Keyword : Satisfaction level, pharmaceutical services, BPJS